Peningkatan kualitas pendidikan anak usia dini: peran pendekatan pedagogis dan kualifikasi guru - Salim, Nur Agus (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2021)
This research explores the role of pedagogical approaches and teacher qualifications on the quality of Early Childhood Education. Through an analysis of current educational literature and policy, this study highlights the importance of a child-centred pedagogical approach, which emphasizes creating learning environments that support and stimulate children's holistic development. Next, this study examines the role of teacher qualifications. Research findings show that the integration of effective pedagogical approaches and highly qualified teachers creates an optimal learning environment, which is critical for supporting children's development at an early age. This study provides insight for curriculum developers, educational practitioners, and policy makers on ways to improve the quality of education at the PAUD level, which is a critical stage in child development.